2005
DOI: 10.1016/j.biopsych.2005.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Encoding Strategy on Episodic Memory and Cortical Activity in Schizophrenia

Abstract: Our findings suggest that a deficit in use of effective strategies influences episodic memory performance in schizophrenia and that abnormalities in functional brain activation persist even when such strategies are applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
77
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 59 publications
16
77
1
Order By: Relevance
“…Thus, orientation to the verbal relatedness of the word-scene pairs significantly improved subsequent recall of the words in both groups. This finding is in line with previous studies of EM in schizophrenia that have reported memory improvement following orientation to beneficial encoding conditions (Bonner-Jackson et al, 2005;Chan et al, 2000;Gold, Randolph, Carpenter, Goldberg, & Weinberger, 1992;Koh & Peterson, 1978;McClain, 1983;Paul et al, 2005;Ragland et al, 2003Ragland et al, , 2006. Such findings have been attributed to an enhancement of strategic memory processes through the manipulation of encoding conditions, as individuals with schizophrenia typically show deficits in generating and applying effective encoding and organizational strategies (Brebion et al, 1997;Brebion, David, Jones, Pilowsky, 2004;Hutton et al, 1998;Iddon et al, 1998;Russell, Bannatyne, & Smith, 1975;Russell & Beekhuis, 1976;Traupmann, 1980).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, orientation to the verbal relatedness of the word-scene pairs significantly improved subsequent recall of the words in both groups. This finding is in line with previous studies of EM in schizophrenia that have reported memory improvement following orientation to beneficial encoding conditions (Bonner-Jackson et al, 2005;Chan et al, 2000;Gold, Randolph, Carpenter, Goldberg, & Weinberger, 1992;Koh & Peterson, 1978;McClain, 1983;Paul et al, 2005;Ragland et al, 2003Ragland et al, , 2006. Such findings have been attributed to an enhancement of strategic memory processes through the manipulation of encoding conditions, as individuals with schizophrenia typically show deficits in generating and applying effective encoding and organizational strategies (Brebion et al, 1997;Brebion, David, Jones, Pilowsky, 2004;Hutton et al, 1998;Iddon et al, 1998;Russell, Bannatyne, & Smith, 1975;Russell & Beekhuis, 1976;Traupmann, 1980).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, EM deficits in individuals with schizophrenia can be somewhat alleviated through interventions that facilitate the use of advantageous encoding strategies, including levels-of-processing manipulations (Bonner-Jackson, Haut, Csernansky, & Barch, 2005;Kubicki et al, 2003;Paul, Elvevag, Bokat, Weinberger, & Goldberg, 2005;Ragland et al, 2003Ragland et al, , 2005, in which participants typically show better memory for items processed ''deeply'' relative to those processed in a ''shallow'' manner. Cues provided during retrieval can also improve EM in schizophrenia (Culver, Kunen, & Zinkgraf, 1986;McClain, 1983;Sengel & Lovallo, 1983;Tompkins, Goldman, & Axelrod, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of any studies reporting increased temporal-VLPFC connectivity, although it occurred at subthreshold levels in one study described above (Meyer-Lindenberg et al, 2005, supplementary online data). While both groups in the current study activated VLPFC equally (Ragland et al, 2005), as in Jennings et al (1998) and Barch et al (2001), other studies have found increased task-related activity of VLPFC in schizophrenia (Kim et al, 2003;Bonner-Jackson et al, 2005;Tan et al, 2005). Overactivation of left inferior frontal cortex has also been observed in a resting PET study (Andreasen et al, 1997), and intriguingly, treatment with either haldoperidol or clozapine reduced VLPFC activity (Lahti et al, 2003).…”
Section: Discussionsupporting
confidence: 52%
“…By strategic encoding, we mean the ability to spontaneously detect and apply effective encoding strategies that would help maintain information in working memory and protect it from interference. The literature on episodic memory gives us good reason to believe that individuals with schizophrenia have difficulty with the spontaneous generation and application of effective encoding strategies [e.g., 97,98]. However, we really have very little idea of the mechanisms by which individuals normally spontaneously generate and apply such encoding strategies.…”
Section: Constructs In Need Of More Basic Researchmentioning
confidence: 99%